Empowering Students’ Speaking Proficiency through a Two-Day English Camp: A Community Service Program in Rural Indonesia - Husnaini; Ermawati; Fidia Ditazam Malik (Lembaga Riset dan Inovasi Masyarakat Madani, 2025)
This study investigates the impact of the English Camp program on enhancing English-speaking proficiency at SMA Negeri 11 Luwu, Indonesia. Conducted over two days, the program focused on interactive learning through communicative tasks such as group discussions, role-playing, and language games. A total of 44 students participated, and their speaking abilities were assessed using pretest and posttest evaluations. The results showed significant improvement in fluency, vocabulary, pronunciation, and confidence. Group 1 and Group 5 exhibited the highest increases in scores, with fluency and confidence showing the greatest gains. The study found that the program was especially effective for lower-proficiency learners, while higher-level learners showed minimal progress due to the ceiling effect. Qualitative data from teacher and student interviews indicated that the camp created a positive and engaging learning environment that encouraged students to use English naturally and confidently. The findings support the efficacy of short-term, immersive programs in improving EFL learners’ speaking skills and highlight the importance of experiential and collaborative learning in language acquisition.